Integrated Path-tracking and Control Allocation Controller for Autonomous Electric Vehicle under Limit Handling Condition - Li, Boyuan; Ahmadi, Javad; Lin, Chenhui; Siampis, Efstathios; Longo, Stefano; Velenis, Efstathios (IEEE, 2021)
In current literature, a number of studies have separately considered path-tracking (PT) control and control allocation (CA) method, but few of studies have integrated them together. This study proposes an integrated PT and CA method for autonomous electric vehicle with independent steering and driving actuators in the limit handling scenario. The high-level feedback PT controller can determine the desired total tire forces and yaw moment, and is designed to guarantee yaw angle error and lateral deviation converge to zero simultaneously. The low-level CA method is formulated as a compact quadratic programming (QP) optimization formulation to optimally allocate individual control actuator. This CA method is designed for a prototype experiment electric vehicle with particularly steering and driving actuator arrangement. The proposed integrated PT controller is validate through numerical simulation based on a high-fidelity CarMaker model on highspeed limit handling scenario.
Keywords: Actuators; Vehicle dynamics; Force; Electric vehicles